Low-Carbon Concrete Development through the Integration of Industrial Waste and Carbon Capture Materials - Mohammad Burhan Hanif; Handini Arga Damar Rani; Surono Surono (International Forum of Researchers and Lecturers, 2024)
This study explores the development of low-carbon concrete by integrating industrial waste materials and CO₂-absorbing minerals to reduce carbon emissions in the construction industry. The research investigates various mix ratios involving fly ash, slag, and CO₂-absorbing minerals, aiming to optimize both performance and sustainability. Experimental methods included compressive strength testing, carbon emission measurement, and durability evaluation. The results indicate that low-carbon concrete formulations achieve up to 45% reduction in carbon emissions compared to conventional concrete, which uses Portland cement. Despite a slight decrease in compressive strength, the optimal mix reached 34 MPa, which is sufficient for structural applications. Durability testing revealed that concrete with CO₂-absorbing minerals showed improved long-term performance compared to other formulations. The findings highlight the potential of using industrial waste materials and carbon capture technologies to create more environmentally sustainable concrete while maintaining necessary structural properties. This study contributes to the growing demand for eco-friendly construction materials and supports the implementation of low-carbon concrete in large-scale industrial applications. Further optimization of mix ratios and long-term performance studies are recommended for broader adoption in the construction industry.